Model Pengembangan Klinik Berhenti Merokok di Wilayah Tengerang Selatan Menggunakan Pendekatan Soft System Methodology - Hannaingtyas, Izza (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2021)
Smoking behaviour has become a habit and culture in Indonesian society. According to WHO (2018), Indonesia is the second country with the largest number of smokers among people aged â‰¥ 15 in the world after France in 2016. The Indonesian Ministry of Health in 2018 stated that the prevalence of smoking was 31.3% in Banten Province, this exceeds the National average of 29.3%. An aim of our analysis was to prevent and reduce smoking behaviour. Public Health Experts has a moral responsibility to overcome problems of smoking behaviour in South Tangerang by â€œSmoking Cessation Clinicâ€. They did this analysis by Soft System Methodology (SSM). It can be used to resolved high complexity problem for change habits and culture in society through strategic thinking and solutions. Result analysis of SSM showed that development model Smoking Cessation Clinic program can be held through electronic education activities by the android application. It designed as a media of alternative development to provide online education to the public. It is hoped that there will be routine educational activities that can be carried out by health cadres, so that the Smoking Cessation Clinic program can be socialized and can be utilized optimally to the community. Keywords: Smoking Behaviour, Smoking Cessation Clinic, Soft System Methodology Abstrak Perilaku merokok sudah menjadi kebiasaan dan budaya masyarakat Indonesia. Menurut WHO (2018), Indonesia merupakan negara kedua dengan jumlah perokok terbesar pada penduduk usia â‰¥ 15 tahun di dunia setelah Perancis pada tahun 2016. Kementerian Kesehatan RI tahun 2018 menyatakan bahwa prevalensi merokok di Provinsi Banten sebesar 31,3%, melebihi rata-rata nasional sebesar 29,3%. Tujuan dari analisis kami adalah untuk mencegah dan mengurangi perilaku merokok. Dokter Spesialis Kesehatan Masyarakat memiliki tanggung jawab moral untuk mengatasi masalah perilaku merokok di Tangerang Selatan melalui